2009
DOI: 10.1136/adc.2009.163709
|View full text |Cite
|
Sign up to set email alerts
|

Trends in overweight and obesity prevalence in Dutch, Turkish, Moroccan and Surinamese South Asian children in the Netherlands

Abstract: The declining prevalence of overweight in Dutch girls may indicate reversal of previous trends in the Netherlands. However, in Turkish children overweight prevalence and obesity is high and increasing. Further public health action is necessary, especially for Turkish children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
92
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 15 publications
(16 reference statements)
12
92
2
Order By: Relevance
“…Prevalence data on overweight/obesity based on self-reported data from 11-, 13-and 15-year-olds were available from twenty-nine of the thirty countries Additional reports on the trends in the prevalence of overweight and/or obesity were found for the following countries (Table 2): Cyprus, Greece, Portugal, Spain (Cuenca), Ireland (Co Kildare), UK (West Scotland), the Czech Republic, Poland (Cracow, East rural), Finland, France, the Netherlands (national, the Hague), Norway (Bergen, Trøndelag) and Sweden (national, Stockholm, Gothenburg) (10,16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence data on overweight/obesity based on self-reported data from 11-, 13-and 15-year-olds were available from twenty-nine of the thirty countries Additional reports on the trends in the prevalence of overweight and/or obesity were found for the following countries (Table 2): Cyprus, Greece, Portugal, Spain (Cuenca), Ireland (Co Kildare), UK (West Scotland), the Czech Republic, Poland (Cracow, East rural), Finland, France, the Netherlands (national, the Hague), Norway (Bergen, Trøndelag) and Sweden (national, Stockholm, Gothenburg) (10,16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) .…”
Section: Resultsmentioning
confidence: 99%
“…2500, SR, N m Linearly in all age/gender groups Finland (29) 1979-2005 12-18--IOTF CSS 3 14, n . 2500, SR, N m Across sociodemographic groups France (30) 1998-2007 3-14 IOTF CSS 3 2, n 1000, SR/M, N -No changes The Netherlands (15) 1980 (31) 1999-2007 3-16---IOTF CSS 3 9, n 8000-10 000, Mr, O mk m Especially in the Turkish, Dutch girls k Norway (Bergen) (32) 1971-2006 4-15--Weight/height CSS 3 2, n 1000-5000, M, O m Lower increase in the older ages Norway (Trøndelag) (33) 1966-1997 14-18 BMI CSS 3 2, n . 5000, M, O m Higher in the upper BMI groups Norway (Trøndelag) (34) 1966-1997 14-18 IOTF CSS 3 2, n .…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Other jurisdictions (e.g., Poland, Australia, the Netherlands, Germany and Denmark) have shown variable changes with either small declines or plateaus in obesity rates. [11][12][13][14][15] Some developing countries are undergoing the same surge in obesity witnessed in Canada from 1978 to 2004. 16 Other investigators have identified higher rates of obesity among Canadian boys using self-reported measures.…”
Section: Discussionmentioning
confidence: 99%
“…4 Results from the United States have shown a decline in obesity rates among toddlers and a plateau in rates among older children; 9,10 stabilization has also been noted in other jurisdictions (e.g., Germany and Australia). [11][12][13][14][15][16] We undertook this study to determine the most recent trends in the prevalence of overweight and obesity among Canadian children using the current WHO weight charts for Canada applied to a representative sample of children.…”
mentioning
confidence: 99%
“…Previous studies showed that the overweight prevalence of Turkish children living in the Netherlands is high with gender differences (in boys 23 %, in girls 30 %) and that unfavourable energy balance-related behaviours (EBRB), i.e. food intake, physical activity (PA) and sedentary behaviour, are common in this group (13)(14)(15) . Participation in PA has a strong socio-economic and ethnic gradient, with children of low socio-economic status or from an ethnic minority being less likely to participate in regular PA than their more advantaged counterparts (16,17) .…”
mentioning
confidence: 99%